Neonatal Fc receptor promoter gene polymorphism does not predict pharmacokinetics of IVIg or the clinical course of GBS. Issue 7 (17th May 2016) - Fokkink, Willem‐Jan R.; Haarman, Annechien E. G.; Tio‐Gillen, Anne P.; van Rijs, Wouter; Huizinga, Ruth; van Doorn, Pieter A.; Jacobs, Bart C.
Abstract: Treatment of Guillain‐Barré syndrome with a standard course of high‐dose intravenous immunoglobulin (IVIg) results in a variable clinical recovery which is associated with changes in serum IgG levels after treatment. The neonatal Fc‐receptor protects IgG from degradation, and a genetic polymorphism in its promoter region that influences the expression of Fc‐receptor, may in part explain the variation in IgG levels and outcome. This polymorphism was determined by polymerase chain reaction in a cohort of 257 patients with Guillain‐Barré syndrome treated with IVIg. We could not demonstrate a relation between this polymorphism, the pharmacokinetics of IVIg, or the clinical course and outcome.